Igreja Metodista Livre: uma igreja evangélica japonesa no processo de inserção no Brasil - Hirakawa, Jorge Issamu (2007)
This work aims to study the role of the Free Methodist Church in Brazil which is a Japanese evangelical church on the insertion process of nikkeis and their descendants in Brazilian society. The first part presents the History of immigration Japanese, In the second part, we analyse the church for immigrant people, In the last part, the Methodism and its beginning in England, United States of America, Japan and Brazil.¸Methodist Church in Brazil and its development among nikkeis and their descendants, followed by a comparison with the Brazilian Council, a branch of the church that deals with people which are not descendant of Japanese